The Impact of Beverage Consumption Habits on Perceived Hunger and Thirst. (29th May 2020) - Widmer, Annaliese; Evenson, Alexa; Heying, Emily; Barnett, Joleen
Abstract: Objectives: The goals were to 1) determine the change in perceived hunger and perceived thirst when consuming carbonated, flavored, and artificially sweetened beverages and 2) to determine if carbonated beverage consumption habits predict perceived hunger and thirst. Methods: Participants (males n  = 14 and females n  = 15) aged 23–65, BMI < 30 kg/m, 2 and not diagnosed with any chronic disease randomly consumed six different beverage treatments (water, carbonated - no flavor [CNF], carbonated - lime flavor [CL], degassed - lime flavor [DL], carbonated - lime flavor with aspartame [CLS], and degassed - lime flavor with aspartame [DLS]) in a single-blinded, cross-over design. Beverage consumption habits of participants were recorded at the first data collection appointment. Participants were asked to eat a breakfast of approximately 400 calories and a subsequent four hour fast on six separate days. A Visual Analog Scale (VAS) was used to measure perceived hunger and thirst at 0 (baseline), followed by beverage consumption, and then measured at 10 and 45 minutes post consumption. ANOVA was used to determine the difference in hunger and thirst perceptions by beverage. Regression determined the influence of beverage consumption habits perceived hunger and thirst at three different time points and the change in perceived hunger and thirst. Results: Perceived hunger and thirst significantly changed over time ( P < 0.001) but did not differ by beverage ( P > 0.05). There was no interaction between time and beverage ( P > 0.05). Perceived hunger scores were 48.59 ± 18.37 and 54.89 ± 18.94 (mean ± SD) at baseline (0 min) and 45 min, respectively ( P < 0.0001). Perceived thirst scores were 54.00 ± 15.22 at baseline (0 min) and 46.37 ± 17.22 at 45 min ( P < 0.0001). Habitual frequency of carbonated beverage consumption did not influence change in perceived thirst, change in perceived hunger, baseline perceived hunger or baseline thirst in the study ( P > 0.05). Conclusions: Perceived hunger significantly increased from baseline to 45-minutes, while perceived thirst significantly decreased from baseline to 45-min. Habitual frequency of consumption of carbonated beverages may have limited impact on changes in perceived hunger and thirst when consuming various beverages. Funding Sources: College of Saint Benedict/Saint John's University Faculty Development Grant and CSB Undergraduate Research Grant.